Energy Impact of ASHRAE's Museum Climate Classes: A Simulation Study on Four Museums with Different Quality of Envelopes. (November 2015) - Kramer, Rick; Schellen, Henk; van Schijndel, Jos
Abstract: ASHRAE's indoor climate design classes for general museums, galleries, archives and libraries are well known: AA (most strict), A, B, C and D (least strict). Museum staff often select class AA, presuming to gain the best overall preservation result that is possible. However, the exact consequences on the energy demand are unknown and therefore barely taken into account when selecting a class. This study quantifies the energy demand of four museum zones with different quality of envelopes (ranging from historical to state-of-the-art museum envelopes), conditioned according to ASHRAE's climate classes. The lower and upper limits of indoor temperature and relative humidity, and the resulting energy demand are determined using building simulations. The conclusions: (i) conditioning according to class B significantly saves energy compared to class A, while class B is still considered as precision control and protects most artefacts; (ii) moving down one class, e.g. from class AA to A, saves relatively more energy for a state-of-the-art building than for a historical building; (iii) Subclasses Ad (larger daily fluctuations) and As (seasonal adjustments, but smaller daily fluctuations) pose the same risk on the collection, but subclass Ad requires less humidification and dehumidification than As, so larger daily fluctuations may be preferred above seasonal adjustments.